1995
DOI: 10.1007/bf00197346
|View full text |Cite
|
Sign up to set email alerts
|

Organic acid exudation as an aluminum-tolerance mechanism in maize (Zea mays L.)

Abstract: Abstract. In this study, the role of root organic acid synthesis and exudation in the mechanism of aluminum tolerance was examined in Al-tolerant (South American 3) and Al-sensitive (Tuxpefio and South American 5) maize genotypes. In a growth solution containing 6 ~tM A13+, Tuxpefio and South American 5 were found to be twoand threefold more sensitive to A1 than South American 3, Root organic acid content and organic acid exudation from the entire root system into the bulk solution were investigated via high-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
207
5
12

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(240 citation statements)
references
References 26 publications
16
207
5
12
Order By: Relevance
“…Pellet et al, 1997) and citric acid (Pellet et al, 1995 ;Ma et al, 1997a). The role of malate in Al tolerance may be to inhibit the blocking of the root cell plasma membrane Ca# + channel (Huang et al, 1996).…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…Pellet et al, 1997) and citric acid (Pellet et al, 1995 ;Ma et al, 1997a). The role of malate in Al tolerance may be to inhibit the blocking of the root cell plasma membrane Ca# + channel (Huang et al, 1996).…”
Section: mentioning
confidence: 99%
“…Several different organic acids, principally oxalic (Ma et al, 1997b), citric (Pellet et al, 1995 ;Ma et al, 1997a) and malic (e.g. Pellet et al, 1997) acids, have been found to be produced in increased amounts by non-mycorrhizal roots exposed to Al.…”
Section: Aluminium and Production Of Oxalic Acidmentioning
confidence: 99%
“…For example, several studies have shown the key role of organic acids in affecting plant tolerance to aluminum (Pellet et al 1995;Ma et al 2001). The role of organic acids in mediating the uptake of Fe 3+ was ascribed to ferric reductase activity and the presence of cation channels (Schmidt 1999).…”
Section: Introductionmentioning
confidence: 99%
“…El ácido secretado puede variar entre especies, por ejemplo, el ácido málico es secretado por plantas de trigo (Delhaize et al, 1993), el cítrico por frijol (Miyasaka et al, 1991) y maíz (Pellet et al, 1995) y el oxálico por trigo (Zheng et al, 1998b). Es posible también que más de dos tipos de AO puedan ser secretados por una misma planta (Ma, 2000) como ocurre en canola, avena, rábano (Zheng et al, 1998a) y triticale , las cuales secretan tanto ácido málico como ácido cítrico.…”
Section: áCidos Orgánicosunclassified